Competitiveness and uncertainty in the NBA and ACB professional basketball leagues - de Saa Guerra, Y.; Martin Gonzalez, J. M.; Garcia-Manso, J. M. (World Congress of Performance Analysis of Sport IX, 2012)
Most research papers are focus on the game itself (in isolation) (Chatterjee & Yilmaz 1999; McGarry et al. 2002; Lebed 2006; McGarry & Franks 2007). Little researches have been conducted from the perspective of competition between teams (Yilmaz & Chatterjee 2000; Ribeiro et al. 2010; de Saá Guerra et al. 2012). According to this, the main aim of a league should be to preserve a high degree of competitiveness within the championship. We understand competitiveness as both the rivalry among teams and the capacity of the teams participating in a league to compete. The greater and more balanced the competitiveness of these teams, the more the league will be able to attract fans, media, and resources, as well as better players, better coaches, etc. This outcome can translate into an increase in the quality of the league. The degree of league competitiveness can act as an indicator of league performance. It is difficult to assess and quantify all elements that yield the final standing (a complex phenomenon). To further explore this issue, we have carried out a work on the study of the competitiveness of the NBA and ACB leagues based on the concept of entropy as the uncertainty or unpredictability of the outcome (the uncertainty level that might exist for each confrontation). We analyzed the degree of uncertainty and randomness of the competition, as a factor of competitiveness. We studied 18 NBA and 14 ACB regular seasons. Both leagues´ entropy levels are high (NBA mean 0.984; ACB mean 0.979), which indicates high competitiveness, but the entropy of the ACB (from 0.972 to 0.987) shows more seasonal variability than the NBA (from 0.985 to 0.990). This is a possible result of greater sporting gradients in the ACB. A league is more competitive when it is more random, meaning when it is harder to predict the final outcome. If the competition is less random, the degree of competitiveness will therefore decrease significantly. The NBA and ACB are very competitive leagues, whose teams are very balanced within each league. This means there is a high degree of uncertainty in knowing the final result. The use of this methodology has proven useful for investigating competitiveness of sports leagues as well as their underlying variability across time.